Lower Prolactin Levels During Cabergoline Treatment are Associated to Tumor Shrinkage in Prolactin Secreting Pituitary Adenoma - Lombardi, M.; Lupi, I.; Cosottini, M.; Rossi, G.; Manetti, L.; Raffaelli, V.; Sardella, C.; Martino, E.; Bogazzi, F. (Hormone and Metabolic Research, 2014)
Dopamine agonists are considered as the first line therapy in prolactin (PRL) secreting pituitary adenomas inducing a normalization of serum PRL and reduction of tumor size. It is known that serum PRL levels, obtained during treatment, are a predictor of tumor shrinkage. Whether PRL suppression below the lower limit of the normal range is related to a greater chance of tumor shrinkage than just its normalization has not been established. This retrospective cohort study was carried out in a tertiary center. Clinical records of 151 patients with PRL-secreting pituitary adenomas (73 micro-, 78 macroadenomas) treated with cabergoline for at least 24 months were analyzed. The adenoma size was analyzed by MRI before and after 24 months of treatment. PRL levels were evaluated every 6 months, assigning a score at each time point (PRL 0=suppressed; 1=normal; 2=above normal). The total score, after 24 months of treatment, was expressed as the sum of the score at each time point and ranged between 0 and 8. A tumor shrinkage was observed in 102/151 patients (67.5%) and it was significantly associated to a lower PRL total score (p=0.021, OR=0.85, CI=0.73–0.97), being significantly more frequent in patients with suppressed PRL than in those with normal PRL (p=0.045, OR=0.42, CI=0.18–0.98) at 24 months. Cabergoline therapy with the goal of achieving PRL levels below the lower limit of normal range can increase the chance to obtain tumor shrinkage of PRL-secreting pituitary adenomas.
Keywords: PRL-secreting adenoma; PRL; dopamine agonists